PEMANFAATAN LIMBAH DAUN NANAS (ANANAS COSMOSUS) SEBAGI ADSORBEN LOGAM BERAT CU - Mayangsari, Novi Eka; Apriani, Mirna; Veptiyan, Egata Dwi (Journal of Research and Technology, 2019)
Pineapple leaf waste (Ananas cosmosus) contains a constituent component in the form of cellulose and lignin. Cellulose, hemicellulose and lignin bind to each other to form lignocellulose. The high cellulose content can be used as an adsorbent through the process of delignification or removal of lignin. This study aims to determine the characteristics and ability of pineapple leaf cellulose to remover heavy Cu metals. Pineapple leaves to be used are equalized to 60 mesh then delignified for 70 and 90 minutes by mixing pineapple powder using 9% NaOH with a ratio of 1:30 (w/v). Pineapple leaves are characterized by chesson, SEM, and XRD analysis. The results of chesson showed that pineapple leaf cellulose had a cellulose content of 25.33% and the delignification time of 70 minutes resulted in the highest cellulose content of 59.12%. The XRD diffractogram showed pineapple leaf cellulose including type I cellulose. The highest degree of crystallinity was obtained by pineapple leaf cellulose with a delignification time of 90 minutes which was equal to 65.98%. The adsorption process is observed with variations in contact time 30; 60; 90; 120 minutes. The highest Cu metal adsorption is pineapple leaves with a delignification process of 70 minutes with a contact time of 90 minutes.